Molecular dynamics methodology for the evaluation of the chemical alteration of wettability of sandstones (2018)
A common practice in the petroleum industry is the waterflooding or another liquids into the formation, to extract the hydrocarbon contained in small pores, through of enhanced/recovery methods (IOR/EOR). In processes of enhanced recovery and condensate banking removal, the main goal is to enable the mobility of production fluids through porous media. For which the concept of wettability is essential since it defines to a great extent how fluids distribution takes place in porous media. In addition, wettability has a huge impact on the variables of field exploitation such as capillary pressure, relative permeability, initial water or residual oil saturation and crude recovery. In this work a methodology to evaluate and represent the wettability alteration phenomena was developed, promoted by the surfactants reaction or adsorption on a surface. The methodology developed through molecular dynamics consist in four procedures: i) tunning the energetic parameter of the interaction potential to achieve a proper description of the initial wettability state, ii) the representation of the adsorption/reaction of the surfactant molecules on the surface, iii) the evaluation of the surface coverage degree, and iv) the contact angle measurements of the liquids on the surfactant-covered surface, in which the wettability alteration promoted by the surfactant was determine. The methodology was validated for surfactants with different types of molecular structure: fluorocarbonated structures, non-ionic surfactants with chain of ethylene oxides (EO). This validation included an analysis of the effect of the chain structure i.e. length and ramifications. To do this, four case studies were evaluated, obtaining excellent agreement between the contact angles measured experimentally and those ones obtained by molecular simulation. The results obtained allow to dilucide the effect of a particular surfactant molecular structure on the performance to promote a specific wetting state.